Analysis the Quality of Human Resources and the Effectiveness of Higher Education Management on Student Academic Performance at Universities in Samarinda, East Kalimantan - Dina Destari (Eastasouth Institute, 2023)
This study's primary focus is on how much a college in Samarinda, East Kalimantan, impacts students' academic achievement in relation to the calibre of its human resources and the efficiency of its administration. This quantitative study explores the impact of human resource quality and college management effectiveness on student academic performance in universities located in Samarinda, East Kalimantan, Indonesia. The research sample included 100 participants representing students, academic staff, and administrative personnel. Data were collected through surveys and academic records, and the analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) path modeling. The results indicate that both